Transforming pharmacy and its societal role in global health contribution - Alves da Costa, Filipa (Archives of Pharmacy, 2022)
Global health prioritizes improving health and achieving equity in health for all people around the globe. The 2015 UN Sustainable Development Goals (SDGs) are call to action that establishes 17 areas where investments are needed to ensure that by 2030 all people enjoy peace and prosperity. SDG 3 (good health and wellbeing) and SDG 4 (quality education) are particularly important for pharmacy transformation. The 21 FIP Development Goals (FIP-DGs) also support global health by transforming the pharmacy profession via the advancement of pharmaceutical practice, sciences and education to achieve cohesion with wider global imperatives underpinned by the SDGs. Academic Capacity and Competency Development are particularly relevant to reshape pharmacy curricula. Pharmacists have traditionally been involved in direct patient care, and progressively moving to advanced practices, including medication review, administration of vaccines and use of pharmacogenetics to individualize drug therapy. There are also emerging roles, namely in the regulatory area and in humanitarian responses. These evolving practices require academia to rethink the undergraduate and postgraduate curricula and reflect on changes needed to become fit for practice. Curricular design demands acknowledging the wider context in which higher education operates, have strategic planning, promote collaboration across other healthcare professions and develop effective means of delivering high quality education that is strongly anchored on competency development with self-directed lifelong learning skills. Commitment to change is needed and a strong investment in continuous quality improvement that may impact on pharmacy practice and in the expansion of the pharmacist’s role as expert in global health.